Sosialisasi Defensive Driving: Membangun Kesadaran Berkendara Aman untuk Keluarga di Rumah( PT PLN Nusantara Power Up Paiton Unit 1.2): Penelitian - Ledi Diana Agustin; Eva Aprilia Cahya Ningsih; Tutik Handayani; Fahrudin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Traffic accidents are one of the leading causes of death globally, particularly in Indonesia, where traffic density is high. This community service activity aims to raise public awareness about the importance of defensive driving techniques. Through socialization and training for families, participants are expected to understand and apply the principles of defensive driving, thereby creating a safer driving environment. The anticipated outcome is an increased understanding of road safety, which, in turn, can reduce traffic accident rates among family members and the community as a whole.